Tetrigimyia minor, a new genus and species of Tachinidae (Diptera) parasitic on Formosatettix larvatus (Orthoptera: Tetrigidae) in Japan - Shima, Hiroshi; Takahashi, Hajime (Zootaxa, 2011)
A new genus and species of blondeliine tachinid, Tetrigimyia minor gen. et sp. nov., is described from Japan. This is a small oviparous tachinid parasitic on adults and larvae of a pygmy grasshopper, Formosatettix larvatus (Orthoptera, Tetrigidae). A brief biological note on this species is added.